As cooperativas de leite da agricultura familiar com interação solidária do Oeste do Paraná: uma análise da retração das instituições nas práticas de gestão - Melo, Aline Milioni de (2018)
This dissertation aims to analyze management practices in the central cooperative of milk of the family agriculture with solidarity interaction of the West of Paraná. The research was developed in ten cooperatives to try to explain the process of closing the six Cooperatives of milk of Family Agriculture with Solidarity Interaction. In order to reach the objective of this work, a theoretical review of the study was carried out, where the study concludes that the management process influenced the closure of cooperatives due to lack of organization, lack of commitment, lack of motivation, poor management of employees and lack of knowledge in the subject.